(3OjhGf GHf ecGfSs - (3GHf ecGfS , YHO GdQMef Hf YHO GdQRGb Hf EHQGgje, aNQ GdOjf CHh GdaQL,J (B794 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi ejR Cgd GdCOH HaUGMI GddSGf hHYO aEf GdeQMhe GdhGdO GHOdg Gddg ef Vjb GddMO HaSjM LfGJg bGajI GdgeRI jGSQ MSg GdTGWi GdefSGH chKQg Ydi GdjhGbHJ ai CTcGd MUHGA s
(3BNQgG (B:s
(3cJGHg Edi HYV CUMGHg hGddg jLYdg SHUQkG ai GdeUGdM bGHdG ddfUGFM eTchQkG dSjQg Je GdOjhGf s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B310s
Keywords: (3GdCOHs